Embracing the Hopelessness of Those Seeking Pastoral Care - De la Torre, Miguel A. (Journal of pastoral theology, 2020)
The uncritical appropriation of Eurocentric philosophical and theological paradigms is detrimental to disenfranchised communities of color. This article argues for a methodology rooted in the hopelessness found within marginalized communities of color. Advocating for an ethics para joder (screw with) disrupts a normative Eurocentric discourse which normalizes and legitimizes Empire.